Optimum Physico-Chemical and Processing Parameters for the Preservation of King Coconut Water - Gunathilake, K. D. P. P.; Rathnayake, R. M. C. N. (International Coconut Community, 2012)
King coconut (Cocos nucifera var. aurantiaca) water is a natural, nutritious and healthy beverage. However, it is underutilized in terms of value addition with extended shelf life. Therefore, an attempt was made to develop the physico-chemical and processing parameters for the value addition of King coconut water with extended shelf life. King coconut water was analyzed for sugar, minerals and vitamin C content based on reviewed methods. Studies were conducted to identify the optimum pH, total soluble solid (TSS), type of acidulant and pasteurization conditions based on sensory properties of the product using semi trained panelists. Processed King coconut water was packed in three different packages and stored at refrigerated (4°C) condition for two months. Changes in pH, TSS and titratable acidity were evaluated in two weeks intervals throughout the storage period. The results showed that optimum pH, TSS, type of acidulant and pasteurization conditions were 4.4, 9, malic acid and 70˚C/15 sec., respectively. The product was microbiologically (less than 50 CFU/ml) safe for consumption even after 8 weeks of storage. These storage studies revealed that the changes in pH, TSS and titratble acidity of King coconut water packed in three packaging materials had no significant difference (p<0.05) during refrigerated storage.